EFISIENSI PENGGUNAAN MODAL KERJA PADA KOPERASI KARYAWAN VICO INDONESIA MUARA BADAK KABUPATEN KUTAI KARTANEGARA - Haryanto Haryanto (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
The background of this research is yet to be in the identification of capital sources cooperative employees of PT . Vico Indonesia. In addition the use of working capital that is not in accordance with usability resulting inefficient use of working capital . Given that the successful management of keuanga not only be seen from one of the company 's financial ratios . Formulation of the problem whether the sources of working capital has been digunakaan in accordance with the needs of the cooperative.Analytical tool in this study using the balance sheet , SHU calculations , changes in the balance sheet , statement of changes in working capital and sources and uses The reports of working capital . It also uses financial ratios consisting of , current ratio , total asset turnover ratio and return on equity .From the calculation of the balance of the comparison can be seen that the amount of current assets in 2012 increased by 15.89 % . Total long-term investments also increased by 10.20 % . The increase in long-term investments influenced by the growing cooperative principal employees of PT . Vico Indonesia. Similarly, the number of assets , the increase in assets of 28.72 % . Total assets also increased by 16.57 % and the number of overall liabilities decreased by 6.53 % . Of some value changes , there are 6 items that decreased ; cash 25.27 % , 7.83%, receivables , operating a motorcycle drove decreased by 9.89 % assistance to the public by 66.67 % in the company's debt by 40 Vico , 21 % . It means more cooperative liquit with increased short-term debt repayment capacity .The results of the calculation of changes in working capital items of current assets decreased by Rp . 399 258 200 , current liabilities decreased to Rp . 272 945 000 . Cooperative employees working capital of PT . Vico Indonesia with Rp . 3890784500 , and the use of capital amounting to Rp . 2.123 billion , in 2009 . It shows the increase in working capital of Rp . 1767784500 .Capital sources cooperative employees of PT . Vico Indonesia also comes from an endowment given by the company . The funds thus become a source of working capital, which does not give rise to liability for the cooperative .Thus the hypothesis " alleged use of already efficient cooperative working capital ( right ) with the purpose of cooperative views of the current ratio , total asset turnover ratio and return on equity " is accepted for the use of working capital in accordance with the desired results